(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Advertisements have been utilized for a long time to impact the purchasing behaviors of the shoppers. Commercials are useful in making the mindfulness and recognition among the consumers of items. Advertising is a vital thing for a brand to get the word out about their business and management. Publicizing today has turned out to be such a connecting with and powerful part of a regular day to day existence. Moreover, advertising can likewise help grow a consumer base which can help in yielding expanded number of offers. Perception in the advertising business is one of the major elements for a business to advance and develop and in this way increment the market esteem. In any case, recognition in advertising incorporates an assortment of components which assume a foremost part in the fruitful development of a business Marketing can be described as a tool for companies to influence the consumer’s perception to the desired direction. The current market situation is characterized by dynamism, growing consumer power, and intense competition. The consumer perception and behavior are changing and therefore need to be constantly monitored and measured. The aim of this article is to scan and measure consumer’s perception while watching a video advertisement. During this experiment, an eye tracking technology was used, which allows capturing a consumer’s gaze. The central part of the research is to measure the brain activity of a consumer based on the EEG (Electroencephalography). EMOTIV Epoc+ is a 14-channel wireless EEG, designed for contextualized research and advanced brain computer interface applications. An advertising campaign from four different mobile operators was used for this purpose. In the conclusion of this article, consumer’s perception of different advertising campaigns are compared and evaluated.